The Proliferation of Undocumented Indonesian Migrant Workers in Batam: A Legal Analysis - Guswandi, Cynthia Putri; Sudirman, Lu; Syarief, Elza (Pascasarjana Ilmu Hukum, Universitas Widya Gama Malang, 2024)
Indonesian Migrant Workers refer to any citizen who is currently or has engaged in employment beyond the borders of Indonesia, receiving wages or compensation. The prevalent issue at hand is the rising number of Indonesian Migrant Workers operating illegally, driven by individuals offering unofficial services with enticing proposals to the public. This study employs a normative legal research approach, utilizing secondary data that encompasses primary legal materials such as Law Number 18 of 2017 concerning the Protection of Indonesian Migrant Workers, secondary legal materials including articles, news, and other literature, as well as tertiary legal materials. Indonesia actively takes part in addressing the concerns of Indonesian Migrant Workers by enacting Law Number 18 of 2017 to ensure the fulfillment of their rights and legal protection, including criminal provisions against wrongdoers. Efforts to address this issue involve public awareness campaigns and legal measures against those engaging in criminal activities.